Multipath mitigation in time-delay estimation via tensorbased techniques for antenna array-based gnss receivers - Lima, Daniel Valle de (2017)
Dissertação (mestrado)—Universidade de Brasília, Faculdade de Tecnologia, Departamento de Engenharia Elétrica, 2017.